2015
DOI: 10.1136/archdischild-2015-308431
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic variation in height: analysis of National Child Measurement Programme data for England

Abstract: Social inequalities were shown in the height of children from white British and Asian ethnic groups. Further evaluation of height in black children is warranted. Action is needed to reduce inequalities in height by addressing the modifiable negative environmental factors that prevent healthy growth and development of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 21 publications
8
20
0
Order By: Relevance
“…However, smoking as the major reason for the finding of short stature should be interpreted with caution as smoking is known to be a proxy marker of socioeconomic status, which has long been known to influence childhood growth. 28,29 In the present study, we showed that Swedish infants and children grew taller than expected based on the WHO growth standard.…”
Section: A Selected Reference Populationsupporting
confidence: 57%
See 1 more Smart Citation
“…However, smoking as the major reason for the finding of short stature should be interpreted with caution as smoking is known to be a proxy marker of socioeconomic status, which has long been known to influence childhood growth. 28,29 In the present study, we showed that Swedish infants and children grew taller than expected based on the WHO growth standard.…”
Section: A Selected Reference Populationsupporting
confidence: 57%
“…In the GrowUp 1990 Gothenburg study, the team was only able to measure adult height in 59% of students in the twelfth school year, and 54% were born in 1989‐1991 and were eligible for inclusion in the present study; out of the latter group, around one‐third fulfilled the inclusion criteria for the reference population. One of the limitations of this approach will be that information based on such a select subpopulation will not tell us about growth in the entire population . Consistent with this, we have previously shown that different subgroups of the 1990 cohort end up with somewhat different adult heights .…”
Section: Discussionmentioning
confidence: 69%
“…For this purpose, all individuals need to be included, even obviously unhealthy ones [2][3][4][5][6]. As such, adult height, as well as the growth pattern of a population, will be excellent indicators of the socioeconomic changes in a society over time [7,8].…”
Section: Why Is Human Growth Pattern Of Interest?mentioning
confidence: 99%
“…There is also a need to explore a broader range of indicators for SEP that are culturally meaningful and capture the individual, family and neighbourhood environment. In the meantime, the persistence of height inequalities, as shown in white children by Hancock et al 5 could have important public health implications for future adult health. Differences in childhood height of the magnitude shown here (∼1.4–1.6 cm) have been linked to elevated risks of cardiovascular disease and some forms of cancer in adulthood.…”
mentioning
confidence: 96%
“…Hancock et al 5 demonstrate that socio-economic inequalities in childhood height still remain, using an impressive data source, the National Child Measurement Programme (NCMP). The NCMP has collated the heights and weights of all 4–5-year-old and 10–11-year-old children attending state-maintained primary schools in England since 2006/2007.…”
mentioning
confidence: 99%